To study the Hardness and Mechanical Properties of Aluminium Composite Reinforced with Titanium Carbide & Graphite. - Sivaraj, Ramaneish (IRC, 2020)
Metal matrix composites are widely used in components of various components of industrial equipment because of their superior material properties like high stiffness to weight ratio and high impact strength and fracture toughness while compared to the conventional material. Even if Al has good mechanical but reinforcement is needed in order to make the composite properties better. Aluminium is often used in the aerospace industry, which has increased concern for fatigue failure. A material can still fail, even though it experiences a force much less than its yield point. Aluminium has good mechanical properties but enhancing with filler metal will make the composite more harder and increase in strength. This research paper shows the mechanical properties of the aluminum composite after reinforced with various percentage of TiC and graphite through powder metallurgy method.